Genomic characteristics of Streptococcus pyogenes isolated from children with respiratory tract infections in a tertiary hospital in Jinshan District of Shanghai， 2013‒2024 - SHEN Yinfang; GONG Jingyu; LI Gang; CHEN Mingliang; ZHU Liqin (Shanghai yufang yixue)
ObjectiveTo analyze the genomic characteristics of Streptococcus pyogenes (GAS) isolated from children with respiratory tract infections in a tertiary hospital in Jinshan District of Shanghai during 2013‒2024, to compare the changes in trend for genomic characteristics before and after 2000, and to provide scientific data for the prevention and control of GAS infections.MethodsGAS strains isolated from children with respiratory tract infections in this hospital were collected from 2013 to 2024. Antimicrobial susceptibility of the isolated strains to 12 antibiotics, including penicillin, cefotaxime, cefepime, linezolid, vancomycin, meropenem, chloramphenicol, ofloxacin, levofloxacin, erythromycin, clindamycin, and tetracycline, was determined using broth microdilution plate method. Besides, whole genome sequencing (WGS) was used to analyze multilocus sequence type (MLST), emm typing, carriage of superantigen genes, mobile genetic element (MGE), carriage of virulence gene, and genomic phylogenetic tree of the isolated strains.ResultsA total of 50 GAS strains were collected and identified from children with respiratory tract infections aged 4‒14 years old, and the resistance rates of those isolates to erythromycin, clindamycin, and tetracycline were 100.00%, 100.00%, and 86.00%, respectively. There were two emm types in the GAS isolates; the emm12 type accounted for 76.00% (38/50), corresponding to ST36 type, and the emm1 type accounted for 24.00% (12/50), corresponding to ST28, ST1274, and new-1 types. There was a statistically significant difference in the constitution of the MLST before and after 2020 (P=0.015). All the isolates carried the superantigen genes speC, speG, ssa, and smeZ. The predominant emm12 isolates belonged to the Clade Ⅱ, carrying the mobile elements ICE-emm12 (harboring erythromycin-resistance gene ermB and tetracycline-resistance gene tetM) and ΦHKU.vir (carrying virulence genes speC and ssa). The emm1 isolates carried the mobile elements ICE-HKU488 (harboring erythromycin-resistance gene ermB and tetracycline-resistance gene tetM) and ΦHKU488.vir (carrying virulence genes speC and ssa), and had close phylogenetical relationships with isolates from Hong Kong, China. No M1UK new clone strains were found. The ST1274 isolates of emm1 were newly discovered in 2020‒2024, and belonged to a separate phylogenetic clade.ConclusionGAS strains isolated from children with respiratory tract infections in a tertiary hospital in Jinshan District of Shanghai exhibit a high resistance to erythromycin, clindamycin, and tetracycline. It is recommended that the clinical treatments change to use other antimicrobial drugs, such as penicillin, third-generation cephalosporins, and fluoroquinolones. During 2020‒2024, a new ST1274 clone strain is discovered in emm1 GAS isolates, without M1UK new clone strains being found. It is essential to continuously concern locally prevalent GAS strains and perform early identification of MLST types to promptly monitor the internal changes of the bacterial population and potential prevalence of new clones.